UTILIZATION OF INDUCTION HEATING IN ELECTRIC STOVE APPLICATION - Fatiatun Fatiatun; Revika Tresiadi; Alva Hidayatullah; Suriani Abu Bakar; Firdaus Firdaus; Kusnanto Mukti Wibowo (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
Electric stoves with the concept of electromagnetic induction use coils to generate magnetic fluxes that can conduct heat. This study aimed to determine how induction-based electric stoves work and the effect of working coil variants on the electromotive force of induction and the temperature of water when cooked. The research method used was an experiment with data analysis using simple and multiple linear regression. The results showed that induction-based electric stoves utilize eddy currents that arise when a ferromagnetic conductor material is placed in the working coil, thus producing heat for cooking. The effect of the working coil on the electromotive force of induction and the temperature of water when cooking uses three working coil variants, namely enamel wire with a diameter of 0.5 mm with a length of 80 m, a diameter of 0.5 with a length of 112 m and a diameter of 1.5 mm with a length of 8 m. After testing, the results showed that the coil variant with a diameter of 0.5 mm and a length of 80 m had a strong influence on the induced emf, and the coil variant with a diameter of 0.5 and a length of 112 m had a substantial impact on the temperature of the water when cooked. This study implies that optimizing the coil configuration, such as using a 0.5 mm diameter enamel wire with a length of 80 m for the induced electromotive force and a 0.5 mm diameter wire with a length of 112 m to increase the water temperature, can improve the efficiency and performance of induction-based electric stoves.